Comments about the concept of collective affectivity - Martínez Chaparro, Ángela María (Pensando Psicología, 2010)
This text is approached from the paradigm of critical social psychology, addresses the issue of collective emotional, revised in fi rst moment the classic concept in psychology about affects understood individual process for then sketch the affectivity as social and collectivity construction. Notion understood mainly from the approaches of Pablo Fernández Christlieb, who allude to the cultural function of the affects in the social life.